2016
DOI: 10.1016/j.annals.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring price elasticities of demand for outbound tourism using competitiveness indices

Abstract: The real exchange rate (REX) has long been used as the proxy for prices in tourism demand models. However it has limitations, particularly when it comes to models of outbound tourism.As an alternative, a price competitiveness index (PCI) is developed and used as a proxy for prices in a model of outbound tourism from Australia. Results obtained show that while REX is statistically insignificant and yields a price elasticity of -0.002, PCI is significant and generates a price elasticity of -1.07. The results obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 34 publications
6
66
3
Order By: Relevance
“…Estimated according to [6,24]. Our results/findings are in sharp contrast with the EKC hypothesis while (at the same time) being completely in line with the results of Seetaram et al [25].…”
Section: Different Scenarios For Reducing Air Transport Co 2 Emissionscontrasting
confidence: 57%
See 1 more Smart Citation
“…Estimated according to [6,24]. Our results/findings are in sharp contrast with the EKC hypothesis while (at the same time) being completely in line with the results of Seetaram et al [25].…”
Section: Different Scenarios For Reducing Air Transport Co 2 Emissionscontrasting
confidence: 57%
“…For example, a study by Seetaram et al [25] points out that a 10% increase in income will cause air transport (and consequently CO 2 emissions) to rise by 23.9% in the long run. Their results clearly show that an increase in income will lead to a greater-than-proportionate rise in air transport.…”
Section: Different Scenarios For Reducing Air Transport Co 2 Emissionsmentioning
confidence: 99%
“…Indeed, there is a plethora of studies that focus their interest on the drivers of outbound tourism, which most commonly use macroeconomic variables, such as unemployment rate, gross domestic product and money supply (see, indicatively, Lim, 1997;Oh, 2005;Halicioglou, 2010;Smeral, 2012;Eugenio-Martin & CamposSoria, 2014;Seetaram, Forsyth, & Dwyer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lim and Zhu (2017) applied dynamic heterogeneous panel data analysis for Singapore and found that long-run income (price) elasticity is positively (negatively) significant. On the other hand, Seetaram et al (2016) introduced the price competitiveness index (PCI) as a new index outperforming the real exchange rate in their model. Yazdi and Khanalizadeh (2017) applied a gravity framework for the USA with 14 countries including our sample countries.…”
Section: Literature Reviewmentioning
confidence: 99%